Pengaruh Motivasi Kerja, Disiplin Kerja, Pelatihan Kerja dan Komitmen Organisasi Terhadap Kinerja Driver Grab Bike di Kabupaten Kubu Raya - Wati, Putri Setia; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of work motivation, work discipline, job training, and organizational commitment on the performance of Grab Bike drivers in Kubu Raya Regency. The method used in this research is a quantitative approach with data collection techniques using questionnaires distributed to a sample of 96 respondents. The sampling technique used is incidental sampling. The data analysis technique applied in this research is multiple linear regression analysis using SPSS 20, with the result: Y = 4.630 + 0.107X1 + 0.163X2 + 0.433X3 - 0.075X4. The results of the study show that, partially, Work Motivation (X1) has a positive effect with a value of 2.629, Work Discipline (X2) has a positive effect with a value of 2.878, Job Training (X3) has a positive effect with a value of 8.390, Organizational Commitment (X4) has a negative effect with a value of -1.852. Simultaneously, work motivation, work discipline, job training, and organizational commitment have a significant effect on the performance of Grab Bike drivers in Kubu Raya Regency, with an F-value of 44.486 and a significance level of 0.000 < 0.05. The R Square (R²) value obtained in this study is 0.662.